PERAN PESANTREN DALAM PEMBENTUKAN KARAKTER BANGSA - Agus Triyono (AS-SALAM, 2017)
Institutions of Islamic boarding school is the oldest in Indonesia. No one knows for sure when these institutions emerged in Indonesia. The educational institutions, led by clerics have two models; modern and salaf. Feature modern Islamic boarding school is to include a general learning courses in the curriculum. While salaf Islamic boarding school did not enter common subjecs in its curriculum. The problem in this research is how the role of Islami boarding school in shaping the morals and character of the Nation. And the purpose of the research was to determine how the role of Islamic boarding school in shaping the morals and character of the Nation. The kind of research is kualitatif. The primary data used is a books that talk about the curriculum and the role of Islamic boarding school. While the secondary data used is the books or the research results directly related to the issue. Analysis method used is descriptive analysis, which is trying to dig the problems that axist and than analyze it. The results showed that Islamic boarding school have a role in shaping the morals dan character of the Nation. It is evidenced by the number of the Nation that was born from Islamic boarding school. Islamic boarding school needs to be preserved and developed. That’s the Islamic boarding school have many roles and provide tangible proof in forming the nation’s moral and character.